The Stylistics of Al-qur'an: The Symbolic Meaning and Function of the Art of Reading Al-qur'an on the Context of Communication - Musta'in Musta'in (Ijtimā iyya Journal of Muslim Society Research, 2018)
The study the stylistics of the Qur'an cannot be separated from the concept of i'jaz al-Quran as a form of uniqueness and privilege of the language of Qur'an. When Qur'an was delivered to the Arab society, they had used high language and literature. By the emergence of the art of reading the Quran (nagham al-Quran) around the world, and it is believed as one of the forms of appreciation of the Qoran, Muslims in Indonesia receive and appreciate it with pleasure. The Musabaqoh Tilawatil Quran (MTQ), whish is held by the governments and non-governmental institutions of all levels, has been carried out on a regular and continuous basis. As a religious text, the Qur'an has a very high literary dimension. The Quran also has some aesthetic and musical-messaging dimensions. This paper attempts to discuss the stylistic styles of language in the aspects of the art of reading the Qoran with a single voice, without the accompaniment of musical instruments, and unrelated to musical tone. This is specifically used for tazyin al-Saut bi tilawah al-Quran. The approach used in this study is Al-Uslub al-Adabi or Literary Stilistica, which focuses on the level of persistence or phonology, which includes phonetics and phonemics. Phonetics is divided into three parts, namely; articulatory phonetic, acoustic phonetics, and auditory phonetics. The discussion on literary stylistics is cannot be separated from emotional aspects, not logical aspects. The analysis of literary stylistics in the art of reading al-Quran (nagham al-Quran) produces the effect of the reader's feelings, sensational feelings and spiritual feeling. Spiritual feeling is divided into religious, ethical, aesthetic, intellectual, social, and personal feeling. Meanwhile, in the aspects of communication generate understanding and scientific knowledge about the principles of transcendent communication, the principle of spiritual communication, the principle of human communication, and finally lead to the Principle of Quranic Communication.